Pengaruh Enterprise Risk Management, Kualitas Audit Eksternal, Dan ESG Disclosure Terhadap Nilai Perusahaan - Rizki Widianto; Christina Dwi Astuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to empirically test the influence of Enterprise Risk Management (ERM), External Audit Quality, and ESG Disclosure on company value with company size and leverage as control variables. This type of research is quantitative causality research using secondary data. The population of this research is mining sector companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The sample taken for this research was 136 which was obtained from the purposive sampling method. The analytical method used is multiple linear regression analysis. The results of this research show that Enterprise Risk Management (ERM) and ESG Disclosure have a positive effect on company value, while External Audit Quality has no effect on company value. The implication of the results of this research is that disclosure of ERM by the company to investors increases the trust of investors and potential investors in the company. Then ESG Disclosure also has a very important role for companies because by highlighting their environmental, social and governance performance, companies can have a better image in the eyes of society in general. Keywords: Company Value, Enterprise Risk Management (ERM), External Audit Quality, ESG Disclosure